„Wer nur den lieben Gott läßt walten“ – ein Rest modaler Melodiebildung? - Marti, Andreas (Jahrbuch für Liturgik und Hymnologie, 1987)
In the hymn-book of the German Protestant Churches (Evangelisches Kirchengesangbuch i. e. EKG) you can find the hymn ,Wer nur den lieben Gott läßt walten‘, which has got an 'e' being the third note of the 2nd line. This is the reason why the whole composition of the hymn seems to be influenced by a modal tendency. The original print has also got an 'e', but in all probability this must be seen as a misprint following the melodies and harmony of other songs which are to be found in this source and its quality of printing.